Using rubber stamps and mobile phones to help understand and change antibiotic prescribing behaviour in private sector primary healthcare clinics in Kenya - Pratap Kumar; Bernadette Kleczka; Mercy Karimi Njeru; Anita Musiega; Phoebe Wekesa; Grace Rabut; Michael Marx (BMJ Global Health)
Background Antibiotic use in primary care can drive antimicrobial resistance (AMR) in the community. However, our understanding of antibiotic prescribing in low- and middle-income countries (LMICs) stems mostly from hospital-based studies or prescription/sales records, with little information available on routine primary care practices. We used an innovative, paper-to-digital documentation approach to deliver routine data and understand antibiotic use for common infections in low-resource primary healthcare clinics (PHCs).Methods Rubber stamps were introduced in nine private sector PHCs serving Nairobi’s informal settlements to ‘print-on-demand’ clinical documentation templates into paper charts. The intervention included one mobile phone per PHC to take and share images of filled templates, guideline compilation booklets and monthly continuing medical education (CME) sessions. Templates for upper respiratory tract (URTI), urinary tract (UTI), sexually transmitted (STI) and gastrointestinal infection (GI) management were used in eight PHCs. Information in templates from 889 patient encounters was digitised from smartphone images, analysed, and fed back to clinicians during monthly CME sessions. UTI charts (n=130 and 96, respectively) were audited preintervention and postintervention for quality of clinical documentation and management.Results Antibiotics were prescribed in 94.3%±1.6% of all patient encounters (97.3% in URTI, 94.2% in UTI, 91.6% in STI and 91.3% in GI), with 1.4±0.4 antibiotics prescribed per encounter. Clinicians considered antibiotic use appropriate in only 58.6% of URTI and 47.2% of GI cases. While feedback did not affect the number of antibiotics prescribed for UTIs, the use of nitrofurantoin, an appropriate, narrow-spectrum antibiotic, increased (9.2% to 29.9%; p<0.0001) and use of broad spectrum quinolones decreased (30.0% to 16.1%; p<0.05).Conclusion Antibiotic use for common infections is high in private sector PHCs in Kenya, with both knowledge and ‘know-do’ gaps contributing to inappropriate prescription. Paper-based templates in combination with smartphone technologies can sustainably deliver routine primary care case management data to support the battle against AMR.